O processo de gestão ambiental em unidades de conservação da natureza: um estudo de caso no Parque Estadual Dunas de Natal - de Medeiros, Andressa Andrade; da Silva, João Gomes; Teixeira, Maria do Socorro Gondim (Revista Gestão da Produção Operações e Sistemas, 2006)
The purpose of this paper is to show the importance of the environmental management applied to the conservation units of nature, focusing on the State Duna Park in Natal, Brazil. It has as a reference a theoretical discussion on the ecological management, environmental valuation and environmental management, proposing the demonstration of a brief report on the environmental externalities in the ecological management process. It uses, as a methodology, the bibliographical and exploratory research and the study case. The results present some measures adopted by the park in order to facilitate the management process of the enterprise, regarding the ecological issues and the principles of economic sustainability. It allows for the development, stimulation and diffusion of the aspects and practices inherent to the environmental management and the ecological awareness. Lastly, this paper considers that the performed activities integrate a systemic process whose results must be constantly followed and adjusted according to the demands caused by the evolution process of the environmental management. Keywords: Environmental management; Conservation units; Duna Park.